KEEFEKTIFAN KALIMAT DALAM KARANGAN EKSPOSISI SISWA KELAS VIII SMP NEGERI 9 PADANG - Zulfikarni, Annisa Ulfasari, Ellya Ratna, (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
The purposes of this study were to (1) describe the effectiveness of the sentence in terms of the accuracy of reasoning categories (a) reasonableness and (b) unity of ideas and (2) to describe the effectiveness of the sentence in terms of language accuracy (a) grammatical accuracy, (b) word precision, and (c) accuracy of spelling in the exposition of students of class VIII 2 SMP Negeri 9 Padang. The method of this research is qualitative. The result of this research is from 167 sentences there are 3 effective sentences and 164 sentences is not effective. In terms of accuracy of reasoning there is no mistake in the student essay. In terms of language accuracy found 164 sentence errors. Thus, the students of grade VIII SMP Negeri 9 Padang have not been able to use sentences effectively.Â Kata kunci: keefektifan kalimat, karangan eksposisi